PROCESS MODELING OF MANAGEMENT OF PRODUCTION POTENTIAL OF ENTERPRISES - SKICHKO, Oleksiy (Herald of Khmelnytskyi National University. Economic sciences, 2024)
The article analyzes the use and principles of organizing the production potential of enterprises with certain properties. It was determined that growth indicators are demonstrated in the conditions of the Ukrainian economy; in the geopolitical situation, Ukraine has maintained a positive rate of development in the economic sphere. GDP growth was helped by investment demand, product exports, the work of the Ukrainian maritime corridor, the expansion of production capacities of the mining industry, and the stability of the energy sector. The stability of the exchange rate and inflation indicators have preserved the stability of the Ukrainian economy. It is claimed that the increase in the efficiency of the production potential of enterprises increases the productivity of the industrial sector, and contributes to the concentration of production, the accumulation of investment in the expansion of reproduction, and the dynamic development of economic systems. It was found that in the process approach, the model of the management of the production potential of enterprises is formulated in terms of interconnected contours of cyclic management or cycle elements of a defined content: analysis of parameters → planning of parameters → provision of parameters and direct management → control of parameters → analysis → the management cycle is restored. The main criteria for evaluating the effectiveness of production potential have been identified, which are detailed in terms of short-term, medium-term and long-term perspectives of enterprises. The provision of management information and data on the state and development of the production potential of enterprises is offered taking into account the parameters of the development of production systems. In the context of solving the problems of the effective functioning of production systems, the recommended process modeling of the management of production potential allows to reorient the focus of management on the implementation of the factors of sustainable growth of enterprises.